1990
DOI: 10.1111/j.1365-2141.1990.tb06364.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mRNA for PDGF B‐chain in human megakaryocytes isolated using a novel immunomagnetic separation method

Abstract: A rapid and simple method has been developed for the separation of pure populations of intact human megakaryocytes from whole bone marrow. Megakaryocytes were specifically recognized using monoclonal antibodies coupled to magnetizable articles. Cells labelled with the magnetizable probe were separated from unlabelled cells by introduction of a magnetic field. The technique yields megakaryocyte suspensions with a purity of greater than 98%. Electron microscope examination showed that the ultrastructure of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…As I have already mentioned, larger than normal megakaryocytes have been observed in bronchial carcinoma [83]. The platelet content of PDGF is determined by the megakaryocyte mRNA for PDGF [63]. In carcinoma of the lung, clubbing and HOA might be influenced by altered PDGF synthetic ability of megakaryocytes, as well as by the right-to-left shunt created by the tumour circulation.…”
Section: Hypertrophic Osteoarthropathy (Hoa)mentioning
confidence: 91%
“…As I have already mentioned, larger than normal megakaryocytes have been observed in bronchial carcinoma [83]. The platelet content of PDGF is determined by the megakaryocyte mRNA for PDGF [63]. In carcinoma of the lung, clubbing and HOA might be influenced by altered PDGF synthetic ability of megakaryocytes, as well as by the right-to-left shunt created by the tumour circulation.…”
Section: Hypertrophic Osteoarthropathy (Hoa)mentioning
confidence: 91%
“…Intramedullar TGF-b is located mainly in megakaryocytes (Fava et al, 1990;Glandwin, 1990). Since the levels of TGF-b1 in the marrow fluid were markedly increased, it is likely that PEG-rHuMGDF directly or indirectly induces the release of TGF-b1 from marrow megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF is a major mitogen for mesenchymal cells such as fibroblasts and smooth muscle cells (Heldin, 1992;Ross et al, 1986). Both cytokines are located mainly in the a-granules of megakaryocyes and platelets (Fava et al, 1990;Glandwin et al, 1990).…”
mentioning
confidence: 99%
“…The human c-sis gene is specifically expressed in very diverse cell-types, such as placental cytotrophoblasts (Goustin et al, 1985), bone marrow megakaryocytes (Gladwin et al, 1990), vascular endothelial cells (DiCorleto and BowenPope, 1983) and smooth muscle cells (Seifert et al, 1984). Previous studies indicated that the amount of 3.5-kb c-sis mRNA is mainly regulated at the transcription level (Colamonici et al, 1986;Daniel and Fen, 1988;Kavanaugh et al, 1988;Harsh et al, 1989;Press et al, 1988;Dirks et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Blood platelets, from which PDGF was originally purified, lack transcriptional machinery. Transcription of the c-sis gene takes place in their precursor cells, the bone marrow megakaryocytes (Gladwin et al, 1990). Human leukemia cell line K562 can be induced to differentiate toward megakaryocytes by treatment with phorbol-esters, which is accompanied by highly increased transcription of the c-sis gene and expression of PDGF (Colamonici et al, 1986;Alitalo et al, 1987).…”
mentioning
confidence: 99%